CHINESE DRAGON: THE FORMATION OF THE SYMBOL OF IMPERIAL AUTHORITY - V. Garrido, Valeriia V. Garrido (Revista Inclusiones, 2021)
This article aims to analyze the formation of the "imperial dragon" symbol in China. Thus, the article solves the following problems: firstly, it demonstrates how the mythological image of the dragon transformed from the heavenly sign into a sign of the will of Heaven, which was necessary for the legitimization of the Chinese emperor’s power. Secondly, it reveals how the ancient texts were using the image of dragon to strengthen the personal authority of the ruler. Thirdly, it examines how the ruling house was using religious cults, in particular, the worshiping of the Dragon King (long wang). The article concludes that the consolidation of the "imperial dragon" symbol was associated with political processes and the need to create a pan-Chinese pantheon of gods and ancestors and systematize various local beliefs and traditions.